Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Because the inverse of function h(x) = 3^x is h^-1 ( x ) = log 3 ( x ) , we solve the equation log 3 ( x ) = 2 ;
3^2 = x;
x = 9 ;
3^2 = x;
x = 9 ;
Use the property of inverse functions:
[tex]h(h^{-1}(x))=x \\ \\ \hbox{if} \\ h^{-1}(x)=2 \\ \hbox{then} \\ h(2)=x \\ \Downarrow \\ h(x)=3^x \\ h(2)=3^2 \\ h(2)=9 \\ \\ \boxed{x=9} [/tex]
[tex]h(h^{-1}(x))=x \\ \\ \hbox{if} \\ h^{-1}(x)=2 \\ \hbox{then} \\ h(2)=x \\ \Downarrow \\ h(x)=3^x \\ h(2)=3^2 \\ h(2)=9 \\ \\ \boxed{x=9} [/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.